HLA-H: Transcriptional Activity and HLA-E Mobilization - Jordier, François; Gras, Delphine; De Grandis, Maria; D'Journo, Xavier-Benoît; Thomas, Pascal-Alexandre; Chanez, Pascal; Picard, Christophe; Chiaroni, Jacques; Paganini, Julien; Di Cristofaro, Julie (Frontiers in Immunology, 2020)
Little attention is paid to pseudogenes from the highly polymorphic HLA genetic region. The pseudogene HLA-H is defined as a non-functional gene because it is deleted at different frequencies in humans and because it encodes a potentially non-functional truncated protein. However, different studies have shown HLA-H transcriptional activity. We formerly identified 13 novel HLA-H alleles, including the H*02:07 allele, which reaches 19.6% in East Asian populations and encodes a full-length HLA protein. The aims of this study were to explore the expression and possible function of the HLA-H molecule. HLA-H may act as a transmembrane molecule and/or indirectly via its signal peptide by mobilizing HLA-E to the cell surface. We analyzed HLA-H RNA expression in Peripheral Blood Mononuclear Cells (PBMC), Human Bronchial Epithelial Cells (HBEC), and available RNA sequencing data from lymphoblastoid cell lines, and we looked to see whether HLA-E was mobilized at the cell surface by the HLA-H signal peptide. Our data confirmed that HLA-H is transcribed at similar levels to HLA-G. We characterized a hemizygous effect in HLA-H expression, and expression differed according to HLA-H alleles; most interestingly, the HLA-H*02:07 allele had the highest level of mRNA expression. We showed that HLA-H signal peptide incubation mobilized HLA-E molecules at the cell surface of T-Lymphocytes, monocytes, B-Lymphocytes, and primary epithelial cells. Our results suggest that HLA-H may be functional but raises many biological issues that need to be addressed.